2004
DOI: 10.1038/emm.2004.18
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and its correlation with clinicopathological features in a series of thyroid tumors prevalent in iodine deficient areas

Abstract: A bstractThyroid tum ors display diverse spectrum of histopathological groups w ith geographic variation in its prevalence. Influence of iodine deficiency (a m ajor causative factor) in its etiology, prevalence, or aggressiveness is debatable w hich reflects the existence of various genetic events in pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…Although it has been suggested that in thyroid tumours, MSI is an important indicator of defects in the MMR system [28], the data presented in this study showed no relationship between MLH1 expression and MSI status. In addition, a previous study on colorectal cancer showed that methylation of another DNA repair gene, MGMT , is also linked to MSI [22,29].…”
Section: Discussioncontrasting
confidence: 87%
“…Although it has been suggested that in thyroid tumours, MSI is an important indicator of defects in the MMR system [28], the data presented in this study showed no relationship between MLH1 expression and MSI status. In addition, a previous study on colorectal cancer showed that methylation of another DNA repair gene, MGMT , is also linked to MSI [22,29].…”
Section: Discussioncontrasting
confidence: 87%
“…However, in most studies a diVerent panel of microsatellite markers for thyroid cancer is used comprising BAT26, BAT-40, TGFbetaRII, hMSH3, and other. Using these markers, MSI and LOH is detected in up to 66% in thyroid tumors (Vaish et al 2003(Vaish et al , 2004Onda et al 2001). Apparently, our microsatellite marker set is inapplicable for MSI and LOH detection in thyroid tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, most of the studies, focused on thyroid carcinoma, have documented that genetic alterations, such as microsatellite instability (MSI) and loss of heterozygosity (LOH), constitute an integral part of thyroid carcinogenesis (25)(26)(27). Although, opposite to FTC (follicular thyroid carcinoma), LOH in PTC is a rather rare mechanism of loss of gene function (26,28).…”
Section: Introductionmentioning
confidence: 99%